Survey of cyclopids (Crustacea, Copepoda) in Brazil and preliminary screening of their potential as dengue vector predators - Luciana Urbano dos Santos; Carlos Fernando S. de Andrade (Revista de Saúde Pública)
INTRODUCTION: Cyclopid copepods are known to be good mosquito controllers, specially as regards the larvae of the dengue vectors Aedes aegypti and Ae. albopictus. MATERIAL AND METHOD: The objective of the study was to survey the local copepod fauna and search for new strains of M. longisetus var. longisetus, comparing the potential of the samples found with the current strain ML-01 against Ae. albopictus larvae, under laboratory conditions. Eleven bodies of water in Campinas, SP, Brazil, were screened for copepods by collecting 1.5 l of water from each of then. The predatory potential of adults copepods was evaluated over 24 h, in the laboratory, for groups of 5 individuals preying upon 30 first instar Ae. albopictus larvae. RESULTS AND CONCLUSION: The following cyclopid species were found: Metacyclops mendocinus, Tropocyclops prasinus, Eucyclops sp, Eucyclops serrulatus, Eucyclops solitarius, Eucyclops ensifer, Macrocyclops albidus var. albidus and Mesocyclops longisetus var. longisetus. The predatory potential of these copepods ranged from nil to 97.3%. A sample collected in the field containing only M. longisetus var. longisetus showed the best control efficiency with no significant difference from a three-year old laboratory culture (ML-01) of the same species evaluated for comparison. The sample with few M. albidus var. albidus was ranked in second place showing an average 25.9% efficiency. The use of copepods in trap tires as dengue vector controllers is discussed.